Methodological characteristics of health technology assessments developed in Peru, 2019-2021 - Taype-Rondan, Alvaro (2022)
Background: Limitations have been reported to comply with good methodological practices in the development of health technology assessments (HTA). Therefore, the objective of the present study was to describe the methodological characteristics of the HTAs carried out in Peru, between 2019-2021. Methods: Descriptive study. We are looking for Peruvian institutions that prepare HTAs whose reports are accessible to the public. We collected the total number of HTAs produced by these institutions per year, and we collected the characteristics of the HTAs produced during the 2019-2021 period. Results: Three Peruvian institutions developed at least three public HTAs between 2019-2021: The Institute for the Evaluation of Technologies in Health and Research (IETSI) (n=142), the Unit for the Analysis and Generation of Evidence in Public Health (UNAGESP) (n=60), and the National Institute of Neoplastic Diseases (INEN) (n=40). The HTAs of UNAGESP did not reach a decision, while 35.9% of those of IETSI and 70.0% of those of INEN concluded in favor of the evaluated technology. All STDs explained the methodology used and performed systematic searches. However, few presented the risk of bias assessment of the included studies (17.4%), the certainty of the evidence (4.6%), or the benefits and harms per outcome (14.4%). None of the HTAs carried out cost studies or made explicit the methodology used to reach the decision. Conclusions: The HTAs evaluated presented favorable methodological aspects and certain shortcomings (in topics such as the report in the evaluation of risk of bias and certainty of the evidence, presentation of benefits and harms by outcome, and explanation of the methodology used to make decisions).